One-Pot Peptide Ligation – Oxidative Cyclization Protocol for the Preparation of Short/Medium Size Disulfide Cyclopeptides - Spengler, Jan (2018)
Native chemical ligation (NCL) employing the N-methylbenzimidazolinone (MeNbz) linker readily provided the linear precursor of a 16-mer peptide that is diﬃcult to obtain by stepwise solid-phase peptide synthesis. NCL and the workup conditions were improved toward a protocol that allows for quantitative removal of the 4-hydroxymercapto- phenol additive and subsequent formation of the disulﬁde bridge in the NCL cocktail by oxidation in air, tolerated by the presence of tris(hydroxypropyl)phosphine.